PENGARUH RELAKSASI NAPAS DALAM DAN AFIRMASI POSITIF TERHADAP KECEMASAN MAHASISWA BARU - Ilyas Zakaria Zakaria; Nunung Siti Sukaesih; Heri Ridwan (Jurnal Keperawatan Abdurrab, 2026)
New students often face various demands for adaptation when entering college, ranging from academic adjustments, changes in the social environment, to separation from family, which can be factors that trigger anxiety. Anxiety that is not handled properly has the potential to interfere with the learning process, sleep quality, and overall psychological well-being. This study aims to analyze the effect of a combination of deep breathing relaxation techniques and positive affirmations on the anxiety levels of new students in the Bachelor of Nursing Program at the Sumedang Campus of the Indonesia University of Education. The study used a pre-experimental design with a pretest–posttest one-group approach and involved 60 new students selected through stratified random sampling. Anxiety levels were measured using the Zung Self-Rating Anxiety Scale (Z-SAS), with the intervention administered over three consecutive days. Data analysis using the Friedman test showed a significant difference in anxiety levels between measurement times (χ² = 180.000; df = 3; p < 0.001), supported by a Kendall's W value of 1.000, which indicates a very strong and consistent effect across all measurement stages. Further tests showed that all measurement time pairs had significant differences (p < 0.001). These results reinforce that the combination of deep breathing relaxation and positive affirmations is an effective non-pharmacological intervention to help new students manage anxiety during the early stages of academic adaptation. Keywords : Anxiety, Deep Breathing Relaxation, Positive Affirmation, New Students.